A Case for Cognitive Entrenchment: To Achieve Optimal Best, Taking Into Account the Importance of Perceived Optimal Efficiency and Cognitive Load Imposition - Phan, Huy P.; Ngu, Bing Hiong (Frontiers in Psychology, 2021)
One interesting observation that we may all concur with is that many experts, or those that are extremely knowledgeable and well-versed in their respective domains of functioning, become ‘mediocre’ and lose their ‘touch of invincibility’ over the course of time. In the world of professional football, for example, it has been argued that an elite football coach would lose his/her air of invincibility and demise after 10-15 years at the top. Why is this the case? There are different reasons and contrasting viewpoints that have been offered to account for this observed demise. One notable concept, recently introduced to explain this decline, is known as cognitive entrenchment, which is concerned with a high level of stability in one’s domain schemas (Dane, 2010). An initial inspection would seem to indicate that cognitive entrenchment is detrimental, potentially imparting evidence of inflexibility, difficulty, and/or a person’s unwillingness to adapt to new contexts (Dane, 2010). This premise importantly connotes the viewpoint that expertise may, in fact, constrain a person from being flexible, innovative, and/or creative to ongoing changes. In this analysis, an expert may experience a cognitive state of entrenchment, facilitated in this case by his/her own experience, knowledge, and/or theoretical understanding of a subject matter. Having said this, however, it is also a plausibility that cognitive entrenchment in itself espouses some form of positivity, giving rise to improvement and/or achievement of different types of adaptive outcomes. Drawing from our existing research development, we propose in this conceptual analysis article that personal ‘entrenchment’ to a particular context (e.g., a football coach’s situated fixation to a particular training methodology) may closely relate to three major elements: self-cognizance of cognitive load imposition, a need for efficiency, and the quest for stability and comfort. As we explore in this conceptual analysis article, there is credence to accept the positivity of cognitive entrenchment – that by nature, for example, a person would purposively choose the status quo in order to minimize cognitive load imposition, optimize efficiency, and/or to achieve minimum disruption and a high level of comfort, which could then ‘optimize’ his/her learning experiences.